2018
DOI: 10.1038/s41598-018-26640-w
|View full text |Cite
|
Sign up to set email alerts
|

Stability and reproducibility of proteomic profiles measured with an aptamer-based platform

Abstract: The feasibility of SOMAscan, a multiplex, high sensitivity proteomics platform, for use in studies using archived plasma samples has not yet been assessed. We quantified 1,305 proteins from plasma samples donated by 16 Nurses’ Health Study (NHS) participants, 40 NHSII participants, and 12 local volunteers. We assessed assay reproducibility using coefficients of variation (CV) from duplicate samples and intra-class correlation coefficients (ICC) and Spearman correlation coefficients (r) of samples processed (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 61 publications
5
114
0
Order By: Relevance
“…SOMAmer proteomic analysis. SOMAscan technology (84,85) was used to simultaneously measure 1129 proteins from each sample at SomaLogic Inc. BALF was diluted with buffer to a standard protein concentration of 20 μg/ml, and 100 μl diluted BALF was equilibrated with a SOMAmers mix (Gold 2010). The SOMAmer mixture allowed for the detection and quantitation of 1129 protein aptamers simultaneously in each sample recorded as relative florescence units (RFU).…”
Section: Methodsmentioning
confidence: 99%
“…SOMAmer proteomic analysis. SOMAscan technology (84,85) was used to simultaneously measure 1129 proteins from each sample at SomaLogic Inc. BALF was diluted with buffer to a standard protein concentration of 20 μg/ml, and 100 μl diluted BALF was equilibrated with a SOMAmers mix (Gold 2010). The SOMAmer mixture allowed for the detection and quantitation of 1129 protein aptamers simultaneously in each sample recorded as relative florescence units (RFU).…”
Section: Methodsmentioning
confidence: 99%
“…[ 1 ] There is increasing interest in the use of novel large scale proteomics platforms to facilitate biomarker discovery for sub‐phenotyping and risk prediction in complex diseases. [ 2 ] Oligonucleotide aptamer‐based platforms, such as the SOMAscan assays marketed by SomaLogic (Boulder, CO), can be used for quantification of >1300 proteins, [ 3–6 ] with >4000 proteins assayed in recent publications. [ 7 ] Aptamers are randomly generated nucleotide sequences that bind specific antigens, mimicking the function of antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…In an independent study, the SomaScan assay with plasma samples has recently demonstrated a high degree of stability and reproducibility. 29 …”
Section: Methodsmentioning
confidence: 99%